MODEL LABORATORIUM SOSIAL LIVING HADIS DALAM PENGUATAN PENDIDIKAN KARAKTER GURU PENDIDIKAN AGAMA ISLAM - Khairil Ikhsan Siregar; Sari Narulita; Ahmad Nur Fahmi; Muhammad Afrijaludin; Muhammad Ryja Baihaqi (Jurnal Manajemen Pendidikan, 2026)
Objective: to develop and evaluate the initial feasibility of a Living Hadith Social Laboratory Model for strengthening the character education of Islamic Religious Education (PAI) teachers, focusing on the limited-implementation stage. Methods: a Research and Development (R&D) approach within a Design-Based Research (DBR) framework was used; an open-ended online questionnaire was administered before (n = 29) and after (n = 23) a training session for PAI and diniyah-madrasah teachers, covering five hadith-based character values, analyzed through descriptive-evaluative qualitative analysis supported by frequency tabulation. Results: 96.6% of pre-test participants had never encountered the model’s term, with thematic hadith knowledge ranging from 27.6–48.3% per value; post-test results showed that 52.2% of participants correctly articulated at least three of the model’s four cyclical stages, accompanied by concrete, contextual classroom follow-up plans. Novelty: this study provides the first empirical evaluation data of a living-hadith-based social laboratory pedagogical model that specifically positions PAI teachers as reflective learners, contributing to the enrichment of applied hadith studies. These findings carry practical implications for the design of teacher-training programs and curriculum development within Islamic education institutions, while underscoring the need for sustained, structured mentoring to ensure that internalization of the model proceeds consistently across all participating cohorts.